Urban Climate Justice : Theory, Praxis, Resistance - Rice, Jennifer L.; Long, Joshua; Levenda, Anthony; Bouma, Dietrich Thomas; Broto, Vanesa Castán; Cox, Savannah; Fitzgerald, Joan; Foster, Sheila; Goh, Kian; Huang, Ping (Geographies of Justice and Social Transformation Series, 2023)
"Arguing that climate injustice is one of our most pressing urban problems, this edited volume explores the possibilities and challenges for more just urban futures under climate change. From displacement within cities through carbon gentrification, to the increasing securitization of elite spaces for climate protection, climate justice and urban justice are intimately connected. Authors in the volume build theoretical tools for interrogating the root causes of climate change, as well as policy failures. Authors also highlight knowledge produced with communities already seeking transformative change and demonstrate meaningful learning from activist groups working to address the socio-natural injustices of climate change impacts. The editors' Introduction situates our current climate emergency within historical processes of colonization, racial capitalism, and heteropatriarchy, while the editors' Conclusion offers pathways forward through abolition, care, and reparations. Where other books focus on the project of critique, this collection advances real world politics to help academics, practitioners, and social justice groups actually imagine, create, and enact more just urban futures under climate change"--
Keywords: Urban policy; Urban ecology (Sociology); Sustainable urban development; Climatic changes : Government policy; Climate justice